LEKSIKOGRAFI BERGAMBAR INDONESIA-GAYO-INGGRIS-ARAB: KONSEP DASAR, FUNGSI, JENIS, DAN ISI KAMUS - Muhammad Hasyimsyah Batubara; Author Mahakarya (Faculty of Cultures and Languages UIN Raden Mas Said, 2021)
The existence of local and vernacular languages in Indonesian of more than six hundreds needs to be defend. It can be done by fostering high loyalty to keep using the language, especially the mother tongue (vernacular) amid the strike of more popular languages. The phenomena of language extinction in the future, such as the decrease in the number of active speakers, the reduction of certain language use, and the ignorance to the mother tongue have become a big problem nowadays. One solution in language preservation is through lexicography or ilm al-shina'ah al-mu'jamiyah or dirasah mu'jamiyah. Lexicography is the art and technique of compiling a dictionary by selecting words to uptake (dakhil), defining word meanings, discussing the completeness of the dictionary components, and giving other information to provide a correct and easy-to-understand meaning of vocabulary. Compiling a dictionary is one of efforts in maintaining the existence of both Indonesian and vernacular language, like Gayo language. Aside from that, arranging Indonesian-Gayo-English-Arabic lexicography, will also help position Indonesian language among global languages. In addition, more Indonesian people may also be able to master second or foreign languages as a vehicle for learning science and modern technology.